A Mapreduce Approach To Deal with Big Data Pre Processing And Classification Problems Based On Evolutionary Algorithms - Saranya, M.S; Jayaveeran, N (International Journal of Computer Sciences and Engineering, 2025)
The big data is a term which is used to describe the exponential growth in data that has occurred recently and it also represents an immense challenge for traditional learning techniques. In order to deal with big data pre processing and classification problems, a novel MapReduce-Neuro Ant Colony (MR-NAC) algorithm was proposed. The proposed algorithm used MapReduce framework to pre process and classify the large dataset which is found to difficult without using the MapReduce framework. The experimentation for the proposed work is carried on two different datasets and results obtained are discussed. The obtained results are much satisfactory which supports the proposed novel algorithm for big data pre processing and classification. AUC and execution time are the two metrics which were used to measure the performance of the proposed MR-NAC Algorithm